Characterization of bleeding in thrombotic thrombocytopenic purpura in the precaplacizumab era: a retrospective nationwide analysis - Amir A. Mahmoud; Mariam Mostafa; Ali Abdelhay; Mouhamed Yazan Abou-Ismail; Shruti Chaturvedi (Research and Practice in Thrombosis and Haemostasis)
Background: The addition of caplacizumab to immune thrombotic thrombocytopenia (iTTP) treatment options has led to a renewed interest in characterizing the epidemiology and risk factors for bleeding in iTTP. Limited data exist on the bleeding risk in iTTP due to systemic underreporting in earlier cohorts. Objectives: To describe the incidence, patterns, and predictors of bleeding in hospitalized iTTP patients independent of caplacizumab use. Methods: We retrospectively analyzed the National Inpatient Sample database (2012-2019) and identified adult patients with a diagnosis of iTTP. Predictors of bleeding were determined by multivariable logistic regression analysis. Results: We identified 3103 iTTP hospitalizations; bleeding occurred in 594 (19.1%), and 157 (5.1%) were characterized by major bleeding. Mucocutaneous bleeding (7.6%) was the most frequent type of bleeding and included heavy menstrual bleeding (2.6%), gingival (2.3%), epistaxis (1.4%), and skin/procedure-related bleeding (1.3%). This was followed closely by gastrointestinal bleeding (5.6%). Patients with bleeding were more likely to be Hispanic, have a weekend admission, and have a higher prevalence of comorbidities. In the multivariable analysis, Hispanic race (odds ratio [OR], 1.48; 1.14-1.91), Asian/Pacific Islander/Native American race (OR, 2.04; 1.51-2.76), coronary artery disease (OR, 1.70; 1.38-2.11), heart failure (OR, 1.39; 1.13-1.72), autoimmune disease (OR, 2.61; 2.08-3.26), Charlson Comorbidity Index ≥ 3 (OR, 2.08; 1.66-2.61), weekend admission (OR, 1.45; 1.22-1.72), and delay ≥2 days in plasma exchange initiation (OR, 1.63; 1.38-1.92), were significantly associated with major bleeding. Conclusions: Bleeding is a relatively common issue in acute iTTP that has not been adequately addressed in existing literature. Further studies are needed to elucidate this risk and associated factors, especially given the incorporation of caplacizumab in the treatment of iTTP.